Efficient techniques of key management and quantum cryptography in RFID networks. Issue 4 (7th May 2014) - Thayananthan, Vijey; Alzahrani, Ahmed; Qureshi, Muhammad Shuaib
Abstract An efficient way of handling security keys using quantum cryptography (QC) for increasing security in radio frequency identification (RFID) networks is being investigated by network security industries. To establish secure RFID network, communication between any two nodes that hold RFID tags and/or readers merged with existing networks should be protected. In order to maximize the data security and secure transmission around RFID network, theoretical model of the quantum key management (KM) system based on RFID is introduced as a proposed research. This model not only manages the secure keys but also it defends passive eavesdropping attacks and other potential attacks. Novelties in this research are security keys of which QC is being utilized in RFID network with continuous key updates. To establish future security around RFID networks, efficient KM protocol and QC, which deal with quantum mathematical procedures and quantum physics, should be analyzed without affecting the legacy. Computational complexities in KM are increasing with the large key sizes, which are manageable through QC. To maximize the security and minimize the complexity in KM, QC with Grover's algorithm is introduced as a method in RFID network environments. So, we have proved that a number of operations with key sizes obtained in KM are reduced. In this proposal, QC will help to reduce the complexity of algorithms used in KM protocols and maximize the security. Copyright © 2014 John Wiley & Sons, Ltd.